Language Strategies for Expressing Humor in The Program “PPG The Next Level” - Rakchat, Sirirat; Kaewjungate, Wuttinun (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2026)
The purpose of this article is for study linguistic strategies for expressing humor in Thai television program named “PPG The Next Level”. The data were collected from all episode recordings of programs distributed through the YouTube website on the Powerpuff GAY channel since the show’s has released on 9 September 2022 to 24 December 2022 for a period of 4 months, a total of 11 recordings. It was found that 6 verbal language strategies for expressing humor: (1) Spoonerism, (2) Hyperbole (3) Equaivocation (4) Unconventional metaphor (5) Homographs and (6) Alliteration, and non-verbal verbal language strategies for expressing humor: (1) Dress up for the show, and (2) Overacting. This study also found that moderators often use friendly language, making viewers feel more at home, It became a prominent feature of the program. These are the moderators signature tools for creating humor and making the show popular. The results of this research study also reflect the habits and values ​​of Thai people who enjoy fun, relaxation, and friendliness.